STRATEGIES FOR IMPROVING INCLUSIVE EDUCATION: LESSONS FROM EARLY CHILDHOOD, ADULT EDUCATION, AND ADMINISTRATIVE PLANNING - GALTIMARI, RUKAIYA GAJI; BIU, HADIZA ALIYU; LADAN, BABANGIDA (Sokoto Educational Review, 2025)
Inclusive education is essential for challenging inequalities of education within various learning environments. This article has reviewed ways of enhancing the education of children with special needs covering early childhood, adult education and administrative frameworks. The focus for early childhood education lies in early childhood special education, identifying the children who require special attention and care, supporting the development of inclusive settings and professional development of teachers. In the context of adult education, the article focused on needs that are tailored to individual learners, the use of learning that can be easily adapted to the learning needs of the learners, and the consequent establishment of learning communities. Good administrative planning is underlined by policy-making, resource management and stakeholder engagement. Examples of best practices from Africa and other parts of the world highlighted successful programmes and best practices. Examined drawbacks include resistance to change, limited resources, and insufficient staff training; possible improvements include technological advancement, policy addition, and better funding. The authors urged educators, policymakers, and administrators to apply the reviewed strategies and recommend directions for further research and development in the field of inclusive education. DOI: https://doie.org/10.0302/SER.2025102433